Ferric hydroxide-based media for removal of toxic arsenic species. Kinetic, equilibrium and thermodynamic studies - Szlachta, Małgorzata; Wójtowicz, Patryk (Oficyna Wydawnicza Politechniki Wrocławskiej, 2018)
Adsorption studies were conducted to assess the feasibility of ferric hydroxide-based material for treatment of highly arsenic-contaminated effluents. The experiments were performed in a batch adsorption regime using a synthetic aqueous solution. The contact time between arsenic ions and the adsorbent, initial concentration of arsenic in treated solution, temperature of solution and adsorbent dose had a significant effect on the adsorption performance in the system. Both the mechanism of the process involved and the rate of As(III) and As(V) adsorption were analyzed based on pseudo-firstand pseudo-second order kinetic models. The adsorption data at constant temperature were described by the Langmuir and Freundlich isotherm equation, and the theoretical adsorption capacity of ferric hydroxide was determined to be 43.75 mg/g and 44.04 mg/g for arsenic(III) and (V), respectively. The estimated thermodynamic parameters, including changes in free energy, enthalpy and entropy, revealed that the adsorption is spontaneous and endothermic under applied experimental conditions.
Environment Protection Engineering. Vol. 44, 2018, nr 4, s. 117-129
Keywords: ochrona środowiska; inżynieria środowiska; czasopisma